Free days for future? Longitudinal effects of working time reductions on individual well-being and environmental behaviour. (August 2022) - Neubert, Sebastian; Bader, Christoph; Hanbury, Hugo; Moser, Stephanie
Abstract: Working time reductions (WTR) are a promising strategy to foster both environmental behaviour and individual well-being. It is unclear, however, whether these possible effects are more likely due to reduced income or to more discretionary time. Moreover, prior studies have only tested the environmental effects of WTR cross-sectionally, and have only tested the well-being effects of WTR including wage compensations. We conducted a longitudinal three-wave study with Swiss employees, including one group who voluntarily reduced their working hours following the first questionnaire. Between-subject analysis suggested that decreased working time is associated with decreased GHG-related behaviours, and increased individual well-being. While the improved GHG-related behaviour is mainly due to reduced income, the well-being effects arise despite lower income. Analyses over time revealed that after reducing their working hours, participants reported increased well-being, more intent-related pro-environmental behaviour, less car commuting, and decreased clothing expenditures. However, no improvement was found regarding other GHG-related behaviours, which are strongly linked to income levels. Thus, reducing standard working time, and simultaneously reducing income, may be a promising strategy. However, voluntarily working a day less per week will probably not reach the full ecological potential of a societal-level WTR. Highlights: We conducted a 10 months quasi experimental longitudinal field study. Working hours and income showed counter-directed effects on well-being. After reducing working hours, work-related burnout decreased. Clothes consumption and commuting decreased, pro-environmental behaviour increased. No effect was found for less malleable environmental behaviour like e.g. housing.